Human monocytes subjected to ischaemia/reperfusion inhibit angiogenesis and wound healing in vitro. (19th January 2020) - Hummitzsch, Lars; Albrecht, Martin; Zitta, Karina; Hess, Katharina; Parczany, Kerstin; Rusch, René; Cremer, Jochen; Steinfath, Markus; Haneya, Assad; Faendrich, Fred; Berndt, Rouven
Abstract: Objectives: The sequence of initial tissue ischaemia and consecutive blood flow restoration leads to ischaemia/reperfusion (I/R) injury, which is typically characterized by a specific inflammatory response. Migrating monocytes seem to mediate the immune response in ischaemic tissues and influence detrimental as well as regenerative effects during I/R injury. Materials and Methods: To clarify the role of classical monocytes in I/R injury, isolated human monocytes were subjected to I/R in vitro (3 hours ischaemia followed by 24 hours of reperfusion). Cellular resilience, monocyte differentiation, cytokine secretion, as well as influence on endothelial tube formation, migration and cell recovery were investigated. Results: We show that I/R supported an enhanced resilience of monocytes and induced intracellular phosphorylation of the prosurvival molecules Erk1/2 and Akt. FACS analysis showed no major alteration in monocyte subtype differentiation and surface marker expression under I/R. Further, our experiments revealed that I/R changes the cytokine secretion pattern, release of angiogenesis associated proteins and MMP‐9 activity in supernatants of monocytes exposed to I/R. Supernatants from monocytes subjected to I/R attenuated endothelial tube formation as indicator for angiogenesis as well as endothelial cell migration and recovery. Conclusion: In summary, monocytes showed no significant change in cellular integrity and monocyte subtype after I/R. Functionally, monocytes might have a rather detrimental influence during the initial phase of I/R, suppressing endothelial cell migration and neoangiogenesis.